2021
DOI: 10.1039/d1ma00073j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in mechanochemical synthesis of mesoporous metal oxides

Abstract: There is a growing interest in mesoporous metal oxides due to their unique properties such as highly accessible porosity, stability, catalytic activity and diversity of nanostructures. Mechanochemical fabrication of mesoporous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 98 publications
0
16
0
Order By: Relevance
“…Introducing porosity in NMs can not only increase their effective surface area but also expose chemically utilizable sites in the bulk for a broad range of applications in catalysis, gas adsorption, environmental remediation, etc. Mechanochemistry-based SSR strategies are highly suitable for the high-throughput design and synthesis of a variety of porous nanostructured materials . For example, Dai et al reported the rapid synthesis of mesoporous alumina (meso-Al 2 O 3 ), which is chemically stable and can retain its porous morphology under high-temperature annealing.…”
Section: Ssrs For the Synthesis Of Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing porosity in NMs can not only increase their effective surface area but also expose chemically utilizable sites in the bulk for a broad range of applications in catalysis, gas adsorption, environmental remediation, etc. Mechanochemistry-based SSR strategies are highly suitable for the high-throughput design and synthesis of a variety of porous nanostructured materials . For example, Dai et al reported the rapid synthesis of mesoporous alumina (meso-Al 2 O 3 ), which is chemically stable and can retain its porous morphology under high-temperature annealing.…”
Section: Ssrs For the Synthesis Of Nanomaterialsmentioning
confidence: 99%
“…Mechanochemistry-based SSR strategies are highly suitable for the highthroughput design and synthesis of a variety of porous nanostructured materials. 1010 For example, Dai et al reported the rapid synthesis of mesoporous alumina (meso-Al 2 O 3 ), which is chemically stable and can retain its porous morphology under high-temperature annealing. In their nonhydrolytic sol−gel strategy (NHSG), aluminum isopropoxide and polymer soft templates (e.g., PEO−PPO−PEO, P123, PEG, etc.)…”
Section: Mechanochemical Synthesis Of Metalmentioning
confidence: 99%
“…This mechanical energy may be in the form of shear, grinding, stretching, or compression. 1–3 The planetary mill used in this study provides a combination of impact and frictional forces which can be varied by different milling parameters. 1,4 When bonds are not broken mechanically within the mill and only mechanical energy changes the system, the synthesis is then termed mechanically activated.…”
Section: Introductionmentioning
confidence: 99%
“…Using the recently proposed pictographic nomenclature for mechanochemical syntheses ( Michalchuk et al, 2021 ), the present redox reaction emphasizing the changes in valence state of the Fe and Mo cations can roughly be represented as 2 SrO + α-Fe 0 + Mo 6+ O 3 + ½ O 2 → → Sr 2 Fe 3+ Mo 5+ O 6 , where the symbols and specify the reaction conditions; namely, they denote the use of “planetary ball mill” and “ambient atmosphere,” respectively. Although in the last few years a surge of investigations in the field of mechanochemistry has resulted in the mechanosynthesis of a variety of complex oxides by forcing a system to acquire metastable and non-equilibrium configurations ( Zhang and Saito, 2012 ; Šepelák et al, 2013 ; Wilkening et al, 2017 ; Porodko et al, 2021 ; Szczȩśniak et al, 2021 ; Tsuzuki, 2021 ; Šepelák et al, 2021 ), there is no report in the literature on the nonconventional mechanochemical route to synthesize Sr 2 FeMoO 6 . Commonly, this material is prepared via a conventional multi-step ceramic route ( Valenzuela et al, 2014 ; Kalanda et al, 2019 ; Alvarado-Flores et al, 2021 ) or various wet chemistry-based routes ( Li et al, 2019 ; Farzin et al, 2020 ; Valdés et al, 2021 ); some of them involve a prolonged heat treatment at considerably high temperatures under reducing atmosphere ( Iranmanesh et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%